1992
DOI: 10.3928/0191-3913-19921101-05
|View full text |Cite
|
Sign up to set email alerts
|

The Ocular Manifestations of the Sturge-Weber Syndrome

Abstract: Sturge-Weber syndrome (SWS) is a rare neurooculocutaneous disorder. The ocular component manifests as glaucoma and vascular malformations of the conjunctiva, episclera, choroid, and retina. The authors reviewed the records of and recalled for examination 51 consecutive patients with a diagnosis of SWS seen at The Hospital for Sick Children, Toronto, Ontario, Canada, from 1980 to 1991. Of the 51 patients, 36 (71%) had glaucoma, 26 experienced onset before 24 months of age and the remainder after 66 months of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(34 citation statements)
references
References 38 publications
1
31
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first study that showed GNAQ mutation in the anterior segment of patients with SWS. Previous studies had found this mutation in choroidal hemangiomas in a case of a patient with SWS 23 24 ; however, choroidal hemangioma did not exist in all patients with SWS, 10 and there were limited evidence that showed choroidal hemangioma occurrence related to the pathogenesis of glaucoma. Our earlier studies found that all SWS scleral surface had scleral vascular malformation.…”
Section: Discussionmentioning
confidence: 81%
“…To the best of our knowledge, this is the first study that showed GNAQ mutation in the anterior segment of patients with SWS. Previous studies had found this mutation in choroidal hemangiomas in a case of a patient with SWS 23 24 ; however, choroidal hemangioma did not exist in all patients with SWS, 10 and there were limited evidence that showed choroidal hemangioma occurrence related to the pathogenesis of glaucoma. Our earlier studies found that all SWS scleral surface had scleral vascular malformation.…”
Section: Discussionmentioning
confidence: 81%
“…Sturge-Weber syndrome (SWS) or encephalo-trigeminal angiomatosis is a rare congenital neurocutaneous disorder that occurs sporadically in ~1 in 50 000 live births. 41 This phakomatosis affects the cephalic venous microvasculature and is characterised by a varying expression of port-wine stains in the distribution of the ophthalmic division (V1) of the trigeminal nerve, 42 ipsilateral venouscapillary abnormalities of the leptomeninges and ocular abnormalities. 43 Ocular complications arise primarily from vascular malformations of the conjunctiva, episclera and choroid.…”
Section: Sturge-weber Syndromementioning
confidence: 99%
“…Other studies have reported the incidence of glaucoma to be as high as 78%. 5 One child with TSC and 3 children with SWS did not have any skin manifestation but were diagnosed based on clinical examination and neuroimaging. These challenging clinical scenarios can lead to diagnostic dilemmas that can easily result in misdiagnosis.…”
Section: Sturge-weber Syndrome (Sws)mentioning
confidence: 99%